2021
DOI: 10.1101/2021.07.21.453295
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The precedence effect in spatial hearing emerges only late in the auditory pathway

Abstract: Background: To localize sound sources accurately in a reverberant environment, human binaural hearing strongly favors analyzing the initial wave front of sounds. Behavioral studies of this 'precedence effect' have so far largely been confined to human subjects, limiting the scope of complementary physiological approaches. Similarly, physiological studies have mostly looked at neural responses in the inferior colliculus, or used modeling of cochlear mechanics in an attempt to identify likely underlying mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…This context makes the recent development of a behavioral biCI rat model (Rosskothen-Kuhl et al 2021) invaluable. Normal hearing rats exhibit behavioral high frequency ("envelope") ITD thresholds which are very similar to those seen in humans (Li et al 2019), and even show very similar "precedence effects" as are seen in human ITD perception (Brown and Stecker 2010;Li et al 2021). This makes rats a well validated model for human binaural hearing, well suited for characterizing the stimulus parameter ranges that allow high levels of ITD sensitivity with high accuracy and reproducibility.…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations
“…This context makes the recent development of a behavioral biCI rat model (Rosskothen-Kuhl et al 2021) invaluable. Normal hearing rats exhibit behavioral high frequency ("envelope") ITD thresholds which are very similar to those seen in humans (Li et al 2019), and even show very similar "precedence effects" as are seen in human ITD perception (Brown and Stecker 2010;Li et al 2021). This makes rats a well validated model for human binaural hearing, well suited for characterizing the stimulus parameter ranges that allow high levels of ITD sensitivity with high accuracy and reproducibility.…”
Section: Introductionmentioning
confidence: 73%
“…In addition, better ITD discrimination in stimuli with rapid onsets is perhaps unsurprising given that, for normal hearing subjects, onset ITDs are normally the most salient (Brown and Stecker 2010). Electrophysiological studies of ITD sensitivity have similarly demonstrated the importance of onset cues in ITD sensitivity at least at the level of the inferior colliculus (Buck et al 2021;Haqqee et al 2021;Li et al 2021) with a fall in ITD sensitivity of between 24-48% when onset responses were excluded (Buck et al 2021). Comparable results were also observed in a behavioral study in normal hearing rats across different pulse rates (Li et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations